The Greek Perspective on Foreign Farm Workers and Agricultural Labor - Lykourgos Chatziioannidis; Maria Partalidou (Proceedings)
Apart from immigrants in Greece who have papers, and perhaps can enjoy greater stability in their lives, there is a very large number of informal immigrants who are faced with the fear of deportation from the country daily. With this in mind, qualitative research was carried out by conducting in-depth interviews with farmers (head of the farm) and quantitative, online research was undertaken using students studying agronomy and/or people who lived in rural areas; the research material was distributed through agricultural/agronomic forums in order to better understand perceptions of agricultural work and find out the main reasons as to why the integration of immigrants and farm workers in Greece is considered to be so difficult.